Dementia‐related agitation in Portuguese public hospitals: A retrospective analysis of 6, 586 hospitalization episodes. (31st December 2021) - Ferreira, Ana Rita; Gonçalves‐Pinho, Manuel; Simões, Mário Rodrigues; Freitas, Alberto; Fernandes, Lia
Abstract: Background: Dementia‐related agitation (DRA) is highly prevalent, disruptive and distressing, being a key cost‐driver of dementia care due to the high risk of emergency hospital admissions and prolonged hospitalizations. These events often prove harmful for dementia patients, resulting in multiple adverse outcomes that heighten the dementia burden. Although emerging studies support the societal and economic toll agitation places on patients, families and healthcare systems, more population‐based studies are needed on how DRA affects healthcare utilization. Thus, this study aimed to describe the hospitalizations with DRA held in mainland Portuguese public hospitals from 2010‐2015. Method: A retrospective observational design was used to analyze a nationwide database officially provided by the Portuguese Administração Central do Sistema de Saúde, IP (ACSS). This database comprises routinely collected healthcare data originally obtained for administrative purposes in all mainland Portuguese public hospitals, including International Classification of Diseases Ninth Revision Clinical Modification (ICD‐9‐CM) diagnostic codes. All inpatient episodes with age ≥65 years and a proxy DRA code of dementia with behavioral disturbance (ICD‐9‐CM 294.11, 294.21), were identified. Descriptive statistics were used to summarize the data. Result: Overall, 6 586 DRA inpatient episodes were analyzed. Most of these were associated with female patients (58.1%), with a mean age of 81±7 years, who have been admitted due to delirium, dementia, amnestic and other cognitive disorders (22.0%), pneumonia (15.0%), urinary tract infections (8.4%), acute bronchitis (5.3%), and acute cerebrovascular disease (4.1%). The median length of stay was 9 days (Q1‐Q3: 5‐17), and a total of 831 patients (12.6%) died during hospitalization. The mean estimated charges per episode were 2 916.5€, representing a total of 19 208 069€ during the study time‐frame. Conclusion: Results corroborate the clinical and economic DRA impact. Nevertheless, data also suggest that a great share of admissions was due to preventable causes, which could have been managed with ambulatory treatment, thereby preventing harmful hospitalizations. To our knowledge, this is the first attempt to characterize how Portuguese patients with DRA use healthcare services, providing useful information to project future healthcare needs. Support: FCT [PD/BD/114555/2016], ERDF through operation POCI‐01‐0145‐FEDER‐007746 funded by COMPETE2020, National Funds through FCT within CINTESIS (UID/IC/4255/2013; UIDB/4255/2020).